Efektivitas Ekstrak Serbuk Kayu Ulin (Eusideroxylon zwageri) dan Sonokeling (Dalbergia latifolia) untuk Mencegah Jamur Pewarna pada Kayu Jabon (Anthocephalus cadamba) - Kusumaningsih, Kartirahayu; Lubis, Lydia Christina; Hadi, Didik Surya (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2025)
One of the problem in using wood species with low natural durability such as Anthocephalus cadamba is their susceptibility to various wood-destroying organisms, including wood-staining fungi (blue stain). These fungi tend to attack wood with high moisture content, causing discoloration into bluish, brownish, or blackish tones, which in turn reduces the quality and usability of the wood. Wood preservation using extracts from sawdust of naturally durable wood species such as Eusideroxylon zwageri and Dalbergia latifolia can serve as an alternative to chemical preservatives. The purpose of this study was to know the effect of wood extract type and preservative solution formulation on the absorption, retention, and the intensity of blue stain fungal attack on A. cadamba wood. The wood was treated using E. zwageri and D. latifolia sawdust extracts at 10%, 20%, and 30% solution formula, and then exposed to blue stain fungi for 1.5 months. The results of the study showed that the two type of wood extracts were effective as wood preservatives against blue stain fungal attacks on A. cadamba wood. The preservative formulation had a significant effect on absorption, retention, and intensity of fungal attack. The highest preservative retention and the lowest intensity of fungal attack were found at the 30% solution formula, with values of 21.020 Kg/m³ for retention and 1.04% for fungal attack intensity.